Behind the Political Agenda. The media analysis of the Law of Victims and Restitution of lands (2013)
After several failed attempts to implement Agrarian Reform in Colombia and one month after his swearing in ceremony, President Juan Manuel Santos presented Congress the Land Restitution chapter of the Victim´s Law, which seeks to return property of their